A Review of Translanguaging as a New Way of Redefining Bi/Multilingualism in South African Classrooms - Kemende Wunseh, Quinta (International Journal of Educational Research Excellence (IJERE), 2023)
South Africa is a multilingual and multicultural country, and the Language in Education Policy (1997) permits any of the 12 official languages to be used as the language of teaching and learning. The purpose of this paper is to examine secondary data about the use of translanguaging in South African multilingual classrooms for a better understanding of course content.  Translanguaging is simply a pedagogical term used to describe the natural ways bilingual/multilingual individuals use their languages in their everyday lives. This paper is discussed qualitatively using a systematic literature review examining several studies that are relevant to the topic.  Both international and national articles and books relating to the topic were identified and analysed. The result from this review shows that translanguaging goes beyond theory to critical pedagogical practice. Also, it shows that the language in education policy (additive bilingualism) has not been able to cater for multilingualism in South African classrooms. Therefore, there is a need to employ translanguaging strategy in the classroom to center the marginalised languages in South African classroom space. The implication of this review is that it offers a blueprint for teachers, education actors, and policymakers to re-imagine South Africa’s bi/multilingualism classrooms through the lens of translanguaging.